Animal exercise studies in cardiovascular research: Current knowledge and optimal design-A position paper of the Committee on Cardiac Rehabilitation, Chinese Medical Doctors' Association - Yihua Bei; Lei Wang; Rongjing Ding; Lin Che; Zhiqing Fan; Wei Gao; Qi Liang; Shenghui Lin; Suixin Liu; Xiao Lu; Yuqin Shen; Guifu Wu; et al. (Elsevier, 2021)
Growing evidence has demonstrated exercise as an effective way to promote cardiovascular health and protect against cardiovascular diseases However, the underlying mechanisms of the beneficial effects of exercise have yet to be elucidated. Animal exercise studies are widely used to investigate the key mechanisms of exercise-induced cardiovascular protection. However, standardized procedures and well-established evaluation indicators for animal exercise models are needed to guide researchers in carrying out effective, high-quality animal studies using exercise to prevent and treat cardiovascular diseases. In our review, we present the commonly used animal exercise models in cardiovascular research and propose a set of standard procedures for exercise training, emphasizing the appropriate measurements and analysis in these chronic exercise models. We also provide recommendations for optimal design of animal exercise studies in cardiovascular research, including the choice of exercise models, control of exercise protocols, exercise at different stages of disease, and other considerations, such as age, sex, and genetic background. We hope that this position paper will promote basic research on exercise-induced cardiovascular protection and pave the way for successful translation of exercise studies from bench to bedside in the prevention and treatment of cardiovascular diseases.